Synthesis and characterization of laser annealed nanoporous silicon-zinc oxide nanoclusters for ultraviolet photodetector application - Thahe, Asad A. (2019)
The main purpose of this study was to synthesize a series of nanoporous silicon (n-PSi) samples on n-type Si (111) wafer using the photo-electrochemical etching (PECE) method, which was effective for the fabrication of a metal-semiconductor-metal (MSM) ultraviolet photodetector. Samples were prepared at fixed etching time (30 min) under varying PECE operating parameters, which included differential current densities (15, 30 and 45 mA/cm2) and variable chemical ratios to achieve optimum growth. The structural, morphological and optical properties of the as-prepared PSi samples were characterized by different analytical techniques. The optimum etching parameters for the growth of n-PSi samples comprise of etching time of 30 min, current density of 45 mA/cm2 and chemical ratio of 2:1:1. The objectives of this study were achieved in three phases. First, a layer of zinc oxide (ZnO) nanoclusters was deposited on the optimally grown n-PSi sample by means of radio frequency (RF) sputtering. The thicknesses of the deposited ZnO nanoclusters layers on n-PSi were varied between 300 nm and 500 nm for annealing temperatures ranging from 600 oC to 900 oC. The optimum thickness and temperature were determined to be 300 nm and 700 oC, respectively. Secondly, platinum (Pt) electrodes were deposited on the n-PSi/ZnO NCs structure via radio frequency sputtering to obtain the MSM (Pt/n-PSi/ZnO NCs/Pt) ultraviolet photodetectors. Finally, the performances of fabricated ultraviolet MSM photodetectors were evaluated using current-voltage (I-V) measurement. The optimum n-PSi and n-PSi/ZnO NCs samples were annealed using a Nd-YAG laser under several shots (pulses) to determine their influence on the structural, morphological, optical and electrical features of the n-PSi/ZnO NCs samples. The photoluminescence spectra of the optimally synthesized n-PSi/ZnO NCs exhibited an intense near band edge emission (violet band centred at 380 nm for bandgap energy of 3.26 V). The I-V characteristics of the fabricated MSM ultraviolet photodetectors were examined in the dark and under ultraviolet light (380 nm) illumination. The results revealed that laser annealing can significantly improved of the performance of the fabricated Pt/n-PSi/ZnO NCs/Pt ultraviolet photodetector in terms of high responsivity (6.35 A/W), photosensitivity (3772.92) as well as faster response time (0.30 s) and recovery time (0.26 s). It was concluded that the proposed MSM ultraviolet photodetectors could be advantageous for various optoelectronic applications.